2020
DOI: 10.1111/1751-7915.13643
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified genes contribute to vanillin tolerance in Saccharomyces cerevisiae

Abstract: We identified that overexpression of GCY1, YPR1, PEX5, and MBF1 enhance the vanillin tolerance of Saccharomyces cerevisiae and explored some of the related mechanisms. This provided novel targets that can be used to improve the performance of S. cerevisiae used in 2nd generation fuel ethanol production, and extended our understanding of the proteins encoded by these genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Mbf1 is a transcriptional coactivator that mediates transcriptional activation by bridging the DNA-binding region of an activator and a TBP (TATA-binding protein) [ 55 ]. However, recently, Liang et al have confirmed that the TBP binding function of Mbf1 was not the reason for the enhancement of vanillin resistance mediated by Mbf1p [ 56 ]. Under stress conditions, Tma17 (also named as Adc17) is the most important chaperone for proteasome biogenesis and assembly in yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Mbf1 is a transcriptional coactivator that mediates transcriptional activation by bridging the DNA-binding region of an activator and a TBP (TATA-binding protein) [ 55 ]. However, recently, Liang et al have confirmed that the TBP binding function of Mbf1 was not the reason for the enhancement of vanillin resistance mediated by Mbf1p [ 56 ]. Under stress conditions, Tma17 (also named as Adc17) is the most important chaperone for proteasome biogenesis and assembly in yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast strain growth capacity on WXML was determined by the spotting assay (Liang et al ., 2021). Overnight cultures were transferred into fresh YPD medium with an initial OD 600 of 0.2 and cultured for another 12 h. The cells were then harvested and washed three times with ddH 2 O and resuspended in ddH 2 O.…”
Section: Methodsmentioning
confidence: 99%
“…The genes involved in mRNA synthesis that directly affect transcriptional control and RNA process are downregulated in response to furfural, and the genes involved in mitochondrial ribosomal proteins are downregulated in response to acetic acid [ 86 ]. High concentrations of vanillin result in the repression of translational and the formation of cytosolic mRNP granules, leading to a reduction in overall protein synthesis levels and the limited translation of mRNAs [ 68 , 101 103 ]. Regulating the expression of these genes to relieve stress-induced transcriptional and translational repression can be beneficial to enhance the tolerance of strain.…”
Section: Response Mechanisms Of S Cerevisiae To St...mentioning
confidence: 99%